Estratégia de capacitação pedagógica do residente: uma perspectiva para melhoria do ensino na Universidade Federal do Rio Grande do Norte - Morais, Ademar Alexandre de (2015)
Studies have shown that resident informally plays the role of teacher. It is estimated that up to 25% of the residents of the time is devoted to teaching, mainly contributing as a facilitator, however, almost the entire medical residency programs in Brazil did not offer teacher training during residency education. This paper aims to introduce educational content initiation to teaching as part of the training of resident physician inserted in residency program of the University Hospital Onofre Lopes (HUOL). It is an exploratory, descriptive and prospective study in HUOL the Federal University of Rio Grande do Norte. Three steps were developed: preparation and planning of a pedagogic course, associated with a motivating technical content (basic and advanced life support); second stage, testing of pedagogical model for medical students; and finally, replication to residents. The interventions were made two practice stations life support with performance evaluation in practical activity through OSPE (Objective Structured Practical Examination). The techniques presented teachings were one-minute preceptor and feedback. Data collection was conducted through a structured evaluation form during the life support stations and at the end of the course, and analyzed using descriptive statistics. The results showed that the feedback and one minute preceptor were considered important for teaching and learning for more than 85% of participants. The feedback from evaluators practices stations added information about the performance and were held appreciatively way, according to 100% of the participants. Positive aspects highlighted by the participants were related to educational content, especially the participants of the first intervention. The time of the lectures of motivating technical content was the most repeated negative. Based on the good acceptance of pedagogical contents, this pioneer teacher training strategy was included in the formal residency program in Cardiology of our institution. It is considered therefore that the educational training model with motivating technical content was feasible and had a good evaluation and acceptance by most participants in both interventions. Thus, we believe that the educational content can be inserted in the formal curriculum of medical residency of other programs at HUOL through the training model developed in this study.